2011
DOI: 10.1002/asl.341
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Model projected changes in 10 m wind speed and direction due to anthropogenic climate change

Abstract: Changes in wind due to global warming may have large geophysical and societal impacts. The 10 m winds from the Coupled Model Intercomparison Project Phase 3 multi-model ensemble are assessed against reanalysis winds and found to exhibit lowest skill over land areas. Maps of future change in mean wind speed, direction and 99th percentile wind speed are presented to convey spatial information as well as the multi-model agreement on sign and magnitude of the change. The utility of these maps in providing context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 22 publications
11
95
0
1
Order By: Relevance
“…Cod larval survival, which is believed to be critical in determining year class strength (50), likely benefits from a prolonged spring bloom increasing the overlap between larval and zooplankton production (51). Enhanced stratification might improve food availability for cod larvae and other predators on zooplankton at high latitudes in spring, but according to our findings, conditions in summer are more unpredictable, in part due to the uncertainty in future wind fields (52,53).…”
Section: Discussionmentioning
confidence: 68%
“…Cod larval survival, which is believed to be critical in determining year class strength (50), likely benefits from a prolonged spring bloom increasing the overlap between larval and zooplankton production (51). Enhanced stratification might improve food availability for cod larvae and other predators on zooplankton at high latitudes in spring, but according to our findings, conditions in summer are more unpredictable, in part due to the uncertainty in future wind fields (52,53).…”
Section: Discussionmentioning
confidence: 68%
“…Long-term changes in the SWS can affect water vapor evaporation and hydrological cycles in some regions (Rayner 2007;McVicar et al 2007;Donohue et al 2010;Niyogi et al 2011;Mclnnes et al 2011;McMahon et al 2013). Previous studies have attributed decreases in pan-evaporation to long-term decreases in SWS in some regions over the past 50 years (Roderick et al 2007;McVicar et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…On an annual basis, mean wind speeds are projected to increase over the entire North Sea region; with the projected changes in mean wind speed typically exceeding 10 %. Despite an overall tendency of increasing mean wind speed in the North Sea region, McInnes et al (2011) identified marked variations between individual models regarding the sign of the change, particularly in the southern North Sea region. In a recent study, Sterl et al (2015) analysed projected change in annual mean wind speeds at 10 m over the southern North Sea region for the RCP4.5 and RCP8.5 scenarios using one GCM.…”
Section: Mean Wind Speedsmentioning
confidence: 87%
“…For extremes of near-surface winds, defined via the 99th percentile of daily mean wind speed, the CMIP3 simulations show an overall slight increase (up to 5 %) in the North Sea region during winter and an overall slight decrease (up to 5 %) during summer (McInnes et al 2011). In this, the projected changes in extreme wind speed are markedly less pronounced than the corresponding changes in mean wind speed when normalised with the climatological values for present-day climate conditions.…”
Section: Wind Extremesmentioning
confidence: 99%
See 1 more Smart Citation